Urgency of Maja Labo Dahu Local Wisdom Value in The Formation of Children's Religious Character in Rada Village - Nofitasari Nofitasari; A Gafar Hidayat; Nurnaningsih Nurnaningsih (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This research is to examine the urgency of the local wisdom value of maja labo dahu in the formation of children's religious character in Rada village, Bima regency. Maja labo dahu, which means